OVERCOMING THE BURDEN OF “VOLYN TRAGEDY” AS AN OPPORTUNITY OF FURTHER DIALOGUE OF COEXISTENCE - Zaporozhchenko, R.; Запорожченко, Р.О. (My University, 2017)
In the present paper the author analyzes dynamics of research and debate as for the issue of “Volyn tragedy”, political reasons for non-decision of the conflict. The concepts of Ukrainian and Polish historiography of “Volyn events” are viewed. Policy of reconciliation is researched as one of the forms of overcoming conflicts in modern times.
Подолання травми "Волині" як можливість діалогу та подальшого співіснування
Keywords: collective memory; historic memory; historiography; policy of reconciliation; “Volyn tragedy”; history